The Legacy of American Copper Smelting : Industrial Heritage versus Environmental Policy - Morin, Bode J. (Book collections on Project MUSE., 2013)
Throughout world history, copper has been a significant metal for a vast number of cultures, from the oldest civilizations on record to the Bronze Age and Greek and Roman antiquity. Though replaced by iron as the primary metal for tools and weapons in ancient civilizations, copper found new resurgence in the nineteenth century when it was discovered to have particularly high thermal and electrical conductivity. Copper mining quickly escalated into a large-scale industry, and because of its vast reserves and innovative mining techniques, the United States seized the reins of global product.